Possible relationship between common genetic variation and white matter development in a pilot study of preterm infants. Issue 7 (2nd April 2016) - Krishnan, Michelle L.; Wang, Zi; Silver, Matt; Boardman, James P.; Ball, Gareth; Counsell, Serena J.; Walley, Andrew J.; Montana, Giovanni; Edwards, Anthony David
Abstract: Background: The consequences of preterm birth are a major public health concern with high rates of ensuing multisystem morbidity, and uncertain biological mechanisms. Common genetic variation may mediate vulnerability to the insult of prematurity and provide opportunities to predict and modify risk. Objective: To gain novel biological and therapeutic insights from the integrated analysis of magnetic resonance imaging and genetic data, informed by prior knowledge. Methods: We apply our previously validated pathway‐based statistical method and a novel network‐based method to discover sources of common genetic variation associated with imaging features indicative of structural brain damage. Results: Lipid pathways were highly ranked by Pathways Sparse Reduced Rank Regression in a model examining the effect of prematurity, and PPAR (peroxisome proliferator‐activated receptor) signaling was the highest ranked pathway once degree of prematurity was accounted for. Within the PPAR pathway, five genes were found by Graph Guided Group Lasso to be highly associated with the phenotype: aquaporin 7 (AQP7), malic enzyme 1, NADP(+)‐dependent, cytosolic (ME1), perilipin 1 (PLIN1), solute carrier family 27 (fatty acid transporter), member 1 (SLC27A1), and acetyl‐CoA acyltransferase 1 (ACAA1). Expression of four of these (ACAA1, AQP7, ME1, and SLC27A1) is controlled by a common transcription factor, early growth response 4 (EGR‐4). Conclusions: This suggests an important role for lipid pathways in influencing development of white matter in preterm infants, and in particular a significant role for interindividual genetic variation in PPAR signaling. Abstract : We apply our previously validated pathway‐ and network‐based statistical methods to discover possible sources of common genetic variation associated with imaging features indicative of structural brain damage. Lipid pathways were highly ranked by Pathways Sparse Reduced Rank Regression in a model examining the effect of prematurity, and PPAR (peroxisome proliferator‐activated receptor) signaling was the highest ranked pathway once degree of prematurity was accounted for. This suggests an important role for lipid pathways in brain injury of prematurity, and in particular a significant role for interindividual genetic variation in PPAR signaling.